1985
DOI: 10.1128/jvi.54.1.7-13.1985
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody that neutralizes poliovirus by cross-linking virions

Abstract: The neutralization of type 1 poliovirus by monoclonal antibody 35-1f4 was studied. The virions were rapidly linked by antibody into oligomers and larger aggregates, followed by slow redistribution of antibody between the immune complexes. The antibody content and infectivity of immune complexes were determined. Remaining single virions were fully infectious and free of antibody. The oligomers and larger aggregates did not signfficantly contribute to the residual infectivity, which therefore correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…The two major consequences of neutralization which have been reported for other picornaviruses include an acidic shift in the pl of virions and the formation of viral aggregates (3,12,16,20,27,28). Analysis of neutralized HRV-14 particles also demonstrated the involvement of these effects in the neutralization of rhinoviruses.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The two major consequences of neutralization which have been reported for other picornaviruses include an acidic shift in the pl of virions and the formation of viral aggregates (3,12,16,20,27,28). Analysis of neutralized HRV-14 particles also demonstrated the involvement of these effects in the neutralization of rhinoviruses.…”
Section: Discussionmentioning
confidence: 80%
“…Keller (17,18) also reported that monovalent Fab fragments obtained by papain digestion were effective in neutralizing poliovirus to a lesser extent than intact, bivalent antibodies, while Mandel (20) reported complete neutralization with Fab fragments obtained from polyclonal antiserum. In contrast, Thomas et al (27) could not prepare Fab fragments that were capable of binding to poliovirus.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several mechanisms of antibody-mediated neutralization have been proposed. Perhaps the simplest is based on aggregation of virions (5,53,54), which generally occurs over a narrow range of antibody/virus ratios. This limited range has raised questions about the role of aggregation in vivo.…”
mentioning
confidence: 99%